Enhancing Community Economy Through Innovation of Processed Cassava Products - Siti Sovia Anwar (FEBI UIN Sunan Kalijaga Yogyakarta, 2020)
The natural resources produced by Padamulya Village are very abundant, but the natural resources owned by Padamulya Village have not been fully utilized by the community, so there is a need for guidance or assistance to the community to exploit the existing potential. One of them is by utilizing processed cassava products that are made into food with high selling price. The method used is the socialization and innovation of cassava processed products. In processing this cassava product, the writer makes cassava churros which is a delicious and healthy snack food. After implementing this program the results obtained are the development of cassava processed products more creative and innovative as well as the surrounding community better understanding how to utilize a potential that is around.Keywords: Product Innovation; Cassava; Community Service